The Role of Sentence Word Order in Developing Arabic Composition Skills: a Pedagogical Perspective - Sahri Sahri; Mohammad Ridwan An Najib; Muhammad Faikhel Abdurrahman; Iqmal Wahyudi (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
Mastering sentence word order is a fundamental aspect of developing Arabic composition skills, particularly for beginner-level learners. However, many Arabic writing instructors focus heavily on essay-based Insya’ exercises without first ensuring students’ proficiency in constructing grammatically sound sentences. This study examines the effectiveness of Sentence Word Order Manipulation as a pedagogical approach to improving students' coherence, fluency, and syntactic accuracy in Arabic writing. Conducted at Pondok Pesantren Darullughah Wadda’wah, this qualitative study involved 30 second-year Ibtida’iyyah (2 Ibt) students with limited prior knowledge of structured Arabic composition. The research employed a classroom-based intervention, incorporating pre-test and post-test assessments, sentence arrangement exercises, classroom observations, and interviews with teachers and students. The findings indicate that structured sentence-building exercises significantly enhance students’ writing fluency, with post-test results showing an 80% improvement in sentence accuracy compared to the pre-test. Additionally, students reported increased confidence in writing, as the approach helped them internalize syntactic rules in a more practical and engaging manner. The study concludes that scaffolded learning models, particularly sentence order exercises, should be integrated into Maharah Kitabah instruction to strengthen students’ foundational composition skills before transitioning to paragraph and essay writing. Future research should explore the long-term impact of this approach on free composition skills and the potential use of technology-enhanced learning tools in Arabic writing instruction.